Cathodoluminescence as an effective probe of carrier transport and deep level defects in droop-mitigating InGaN/GaN quantum well heterostructures. (15th February 2019) - Zhao, Zhibo; Singh, Akshay; Chesin, Jordan; Armitage, Rob; Wildeson, Isaac; Deb, Parijat; Armstrong, Andrew; Kisslinger, Kim; Stach, Eric A.; Gradečak, Silvija
Abstract: Commercial InGaN/GaN light emitting diodes continue to suffer from efficiency droop at high current densities, and urgently require enhanced structural-optical toolsets for active region characterization. In our work, we measure delayed (tens of seconds) cathodoluminescence which is influenced by carrier transport and deep level defects. Further, we observe that drops in efficiency are not correlated with quantum well (QW) width fluctuations. To explain the rise dynamics, we propose a model involving filling of deep level defects and simultaneous reduction of built-in field within the multi-QW active region. These measurements yield insights into carrier transport, efficiency-reducing defects, and QW band structure.